The thyroid hormone receptor β-selective agonist GC-1 does not affect tolerance to exercise in hypothyroid rats - Gonçalves, Alexandre (2015)
Objective: investigate the effect of GC-1 on tolerance to exercise in rats with experimental hypothyroidism. Materials and methods: hypothyroidism was induced with methimazole sodium and perchlorate treatment. Six groups with eight animals were studied: control group (C), hypothyroid group without treatment (HYPO); hypothyroidism treated with physiological doses of tetraiodothyronine (T4) or 10 times higher (10×T4); hypothyroidism treated with equal molar doses of GC-1 (GC-1) or 10 times higher (10×GC-1). After eight weeks, each animal underwent an exercise tolerance test by measuring the time (seconds), in which the rats were swimming with a load attached to their tails without being submerging for more than 10 sec. After the test, the animals were killed, and blood samples were collected for biochemical analysis, and the heart and soleus muscle were removed for weighing and morphometric analysis of the cardiomyocyte. Results: hypothyroidism significantly reduced tolerance to exercise and, treatment with GC-1 1× or T4 in physiological doses recover tolerance test to normal parameters. However, high doses of T4 also decreased tolerance to physical exercise. Conversely, ten times higher doses of GC-1 did not impair tolerance to exercise. Interestingly, hypothyroidism, treated or not with T4 in a physiological range, GC-1 or even high doses of GC-1 (10X) did not change cardiomyocyte diameters and relative weight of the soleus muscle. In contrast, higher doses of T4 significantly increased cardiomyocyte diameter and induced atrophy of the soleus muscle. Conclusion: unlike T4, GC-1 in high doses did not modify tolerance to physical exercise in the rats with hypothyroidism.